Palliative care in patients with rheumatological conditions (Research, Society and Development, 2023)
This article aims to understand how it is possible to reduce suffering and offer a dignified life trajectory to patients with rheumatological diseases. Rheumatic diseases increase as the rate of population aging increases, on multiple occasions becoming an impediment to the quality of life of many citizens. Palliative Care is known to provide patients with relief from the symptoms, pain and stress of a serious illness, regardless of diagnosis. In order to provide quality of life for individuals. Today, palliative medicine has a broad vision that includes patients with degenerative diseases, such as those related to connective tissue inflammation, which constitute a group of diseases that fall under rheumatological care. The frequent association with other pathologies and treatment complications leads to progressive harm to patients, with organ deterioration and even death.